New-onset diabetes mellitus after renal transplantation - Goldmannova, Dominika; Karasek, David; Krystynik, Ondrej; Zadrazil, Josef (Biomedical papers, 2016)
Background and Aim. Diabetes mellitus is a very common metabolic disease with a rising incidence. It is both a leading cause of chronic renal disease and one of the most serious comorbidities in renal transplant recipients. New-onset diabetes after renal transplantation (NODAT) is associated with poor graft function, higher rates of cardiovascular complications and a poor prognosis. The aim of this paper is to review current knowledge of NODAT including risk factors, diagnosis and management.Methods: A MEDLINE search was performed to retrieve both original and review articles addressing the epidemiology, risk factors, screening and management of NODAT. We also focused on microRNAs as potential biomarkers of NODAT.Results and Conclusion: Understanding the risk factors (both modifiable-e.g. obesity, viruses, and unmodifiable-e.g. age, genetics) may help reduce the incidence and impact of NODAT using pre- and post-transplant management. This can lead to better long-term graft function and general transplant success.
Keywords: diabetes mellitus; renal transplantation; NODAT; microRNA